Analgesic drugs: What quality of information is present on the Internet? (Research, Society and Development, 2021)
The internet enables the search for several subject types, including health and drug utilization. These information are spread generally without reliability and scientific basis, that can encourage self-medication and indiscriminate medicine use. This was a cross-sectional study, carried out through application of tools that evaluated the quality of global health information and the specific content about analgesic drugs on 98 Brazilian websites. Among the most cited drugs on websites, nonsteroidal anti-inflammatory drugs (83.67 %), acetaminophen (47.96 %) and opioids (47.96 %) stood out. All websites described pharmacological treatment options for pain, however, most websites did not mention any adverse reactions or contraindications for painkillers use. Information on opioid addiction and tolerance risk was present only in 18.37 % of websites. Considering all the indicators evaluated, no website was considered to be of good quality, even those with a quality certification seal. These results showed important shortcomings on health and drugs information published on internet, which can lead to analgesics inappropriate use, adverse effects and even intoxications events. This reinforces the need to control this information and to adopt minimum quality criteria for the websites, aiming to minimize health risks, drug irrational use and to contribute for lay public’s safety.